The effect of primordial non-Gaussianity on the skeleton of cosmic shear maps - Fedeli, Cosimo; Pace, Francesco; Moscardini, L.; Grossi, M.; Dolag, K. (Monthly notices of the Royal Astronomical Society, 2011)
We explore the imprints of deviations from Gaussian primordial density fluctuations on the skeleton of the large-scale matter distribution as mapped through cosmological weak lensing. The skeleton of the large-scale structure traces its filamentary structure and thus provides a complementary piece of information with respect to e.g. the simple probability distribution function or the peak number counts. We computed the skeleton length of simulated effective convergence maps covering ∼35 deg2 each, extracted from a suite of cosmological n-body runs with different levels of local primordial non-Gaussianity. The latter is expected to alter the structure formation process with respect to the fiducial Gaussian scenario, and thus to leave a signature on the cosmic web. We found that alterations of the initial conditions consistently modify both the cumulative and the differential skeleton length, although the effect is generically smaller than the cosmic variance and depends on the smoothing of the map prior to the skeleton computation. Nevertheless, the qualitative shape of these deviations is rather similar to their primordial counterparts, implying that skeleton statistics retain good memory of the initial conditions. We performed a statistical analysis in order to find out at what confidence level primordial non-Gaussianity could be constrained by the skeleton test on cosmic shear maps of the size we adopted. At 68.3 per cent confidence level we found an error on the measured level of primordial non-Gaussianity of ΔfNL∼ 300, while at 90 per cent confidence level it is of ΔfNL∼ 500. In both cases we ignored the effects of observational noise and degeneracy with other cosmological parameters. While these values by themselves are not competitive with the current constraints, weak lensing maps larger than those used here would have a smaller field-to-field variance, and thus would likely lead to tighter constraints. A rough estimate indicates ΔfNL∼ a few tens at 68.3 per cent confidence level for an all-sky weak lensing survey.
Gesehen am 03.05.2022